INTERCULTURAL NURSING IN CHAOS ENVIRONMENT: CASE REPORT - Uysal, Duygu Akbaş; Aykar, Fisun Şenuzun (PROFESSIONAL STUDIES: Theory And Practice, 2024)
The epidemic caused by the Covid-19 virus released in December 2019 was declared as a pandemic by the World Health Organization. The rapid spread of the virus unexpectedly and causing high deaths has led to a difficult process in the field of health. Societies, which are a social and cultural phenomenon, have also been affected by this epidemic in different ways. The phenomenon of health is not only a stable state of medical procedures, but also a dynamic concept where different cultures come together. Defending that if nurses do not take into account the cultural differences in the individual or society, the care to be given will not be effective, Leninger says that care should have the universal characteristics of the human structure under all conditions. In this sense, the aim of intercultural nursing is to provide culturally appropriate care. In this case, there are problems in health caused by the communication problem encountered in an Angolan patient who was hospitalized in the burn service when the coronavirus disease 2019 (COVID-19) was pandemic.